Electrolyte disturbances and lipid profiles in ischaemic and hemorrhagic stroke patients in Aisyiyah Bojonegoro Hospital, Indonesia - Setyawati, Yunita Dwi; Mastura, Rila Ruis (International Journal of Research in Medical Sciences, 2020)
Background: The prevalence of stroke continues to increase every year. Electrolyte imbalance and metabolic disorder can cause high morbidity and mortality of stroke. There are very few studies conducted on serum electrolytes and lipid levels in stroke patients. Authors aimed to know the electrolyte disturbance and lipid profiles in acute stroke. Methods: Retrospective case analysis was used in this study. Patients who diagnosed with hemorrhagic and ischaemic stroke in Aisyiyah Bojonegoro Hospital from January to September 2019 were selected trough electronic medical records system. Authors examine the electrolyte levels and lipid profiles. Patients with a previous history of stroke, complication that might affect electrolyte level and incomplete data in medical records were excluded. Independent T-test or Mann Whitney test were used to analyze the difference of parameters between hemorrhagic and ischaemic stroke patients. P value was considered as significant at p<0.05. Results: Most common electrolyte imbalance in both hemorrhagic and ischaemic stroke was hypokalemia which is statistically significant. Comparison between stroke patients was statistically significant for mean potassium and high density lipoprotein (HDL), while other mean serum values were not different. Potassium significantly lower (p=0.002) in hemorrhagic stroke and HDL significantly lower (p=0.034) in ischaemic stroke. Conclusions: This study reveals that hypokalemia was higher in hemorrhagic stroke and HDL was lower in ischaemic stroke. Regular monitoring of lipid levels in patients with high risk factors and correction of electrolytes imbalance for stroke patients will help in decreasing the mortality and morbidity.